PEMBELAJARAN MENYIMAK BERBASIS PENDEKATAN KONTEKSTUAL - Rosdawita, Rosdawita (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2015)
The reality of today’s student listening skills have not been so encouraging. The con- dition occurs because the applied learning scenarios do not support the creation of a fun learning situation. Learning to listen more unappealing if the learning situation is monotonous. By applying contecstual approach teaching and learning (CTL) in a predictable learning listening skills of students can be improved because CTL is one of the concepts that help faculty learn the material being taught to associate with real- world situations students and encourage students to make connections between the knowledge possessed by its application to the their lives as a prospective teacher. Keywords: student, listening, contecstual approach